Biology and Ecosystem Conservation: The Role of Life Sciences in Addressing the Destruction of Nature - Efendi, Harja (PT. Anagata Sembagi Education, 2025)
This study aims to examine the role of biology in ecosystem conservation and efforts to overcome environmental degradation through an evidence-based scientific approach. The method used is the Systematic Literature Review (SLR), which allows a comprehensive analysis of various relevant previous articles and studies. Literature was collected from leading academic databases, such as Google Scholar, PubMed, ScienceDirect, and JSTOR, with a focus on publications in the last five years that discuss ecosystem conservation, environmental restoration, and the use of biology in environmental conservation. The main keywords used in the search include